2013
DOI: 10.2147/opth.s41607
|View full text |Cite
|
Sign up to set email alerts
|

Developmental dyslexia and vision

Abstract: Developmental dyslexia affects almost 10% of school-aged children and represents a significant public health problem. Its etiology is unknown. The consistent presence of phonological difficulties combined with an inability to manipulate language sounds and the grapheme–phoneme conversion is widely acknowledged. Numerous scientific studies have also documented the presence of eye movement anomalies and deficits of perception of low contrast, low spatial frequency, and high frequency temporal visual information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 107 publications
0
25
1
3
Order By: Relevance
“…18 A review of the literature in 2013 found that poor perception of low contrast was associated with dyslexia. 24 These results were based on small school-based studies, with participants generally described as having "reading difficulties" rather than specifically dyslexia, and were not corroborated by the current study. …”
contrasting
confidence: 89%
See 2 more Smart Citations
“…18 A review of the literature in 2013 found that poor perception of low contrast was associated with dyslexia. 24 These results were based on small school-based studies, with participants generally described as having "reading difficulties" rather than specifically dyslexia, and were not corroborated by the current study. …”
contrasting
confidence: 89%
“…Previously literature reviews in general have been based on school-based studies involving small numbers of children and controls. 24 The ALSPAC study took place in a defined geographic area and was comparable with the United Kingdom as a whole in the 1991 census; however, the number of nonwhite families in ALSPAC was disproportionately small. 36 Noncycloplegic refraction was used to define refractive error.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…En este proceso la atención (guiada desde arriba) a estas dimensiones espaciotemporales por parte de las áreas primarias auditivas y visuales modula las neuronas de las áreas sensoriales primarias (abajo) que envían la información procesada a áreas corticales superiores para su correcto almacenamiento, lo que facilita el reconocimiento ante el mismo estímulo en el futuro. La atención espacial afecta no solo a la habilidad para detectar el estímulo, sino también para representar mentalmente este estimulo (Quercia, Feiss y Michel, 2013) y, por tanto, para almacenarlo y recuperarlo.…”
Section: Dimensión Espacialunclassified
“…Este déficit audiovisual para el procesamiento de la información espacio-temporal es la causa de un lento reconocimiento de las letras y una pobre habilidad para secuenciar las letras y sus sonidos que, a su vez, deriva de un déficit en sincronización sensorial (sensory timing) de los imputs visuales durante la lectura y los sonidos de la palabra cuando se escuchan, esto es, un déficit en el procesamiento temporal (Stein, 2018). El déficit en el procesamiento temporal del habla oral también es explicado por la por la teoría magnocelular, puesto que este contribuye a la rápida integración de la información visual mientras leemos permitiendo un procesamiento eficiente, sincrónico, de la información visual espacial y temporal y puede intervenir con un papel equivalente con la información auditiva (Quercia, Feiss y Michel, 2013).…”
Section: Propuesta Diferenciadora Y Consecuencias Cognitivas Del Défiunclassified